2014
DOI: 10.1001/jama.2014.13513
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Skilled Nursing Facility Quality Indicators and Hospital Readmissions

Abstract: Importance Hospital readmissions are common, costly, and potentially preventable. Little is known about the association between available SNF performance measures and the risk of hospital readmission. Objective To measure the association between SNF performance measures and hospital readmissions among Medicare beneficiaries receiving post-acute care at U.S. SNFs. Design Using national Medicare data, we examined the association between SNF performance on publicly available metrics (SNF staffing intensity, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 33 publications
9
155
2
Order By: Relevance
“…This finding is consistent with previous work demonstrating that for-profit SNF have higher rates of readmission generally. 41–43 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous work demonstrating that for-profit SNF have higher rates of readmission generally. 41–43 …”
Section: Discussionmentioning
confidence: 99%
“…14 Pay-for-performance systems, such as the Physician Quality Reporting System, use several quality measures relating to prostate cancer care, including the avoidance of bone scans in patients diagnosed with low-risk disease. 15 Although investigations in other disciplines suggest that quality indicator adherence may not be associated with improved outcomes, 16,17 they are considered benchmarks of high-quality care. 15 As we shift from a fee-for-service model to value-based care, 18 and Medicare payments become increasingly tied to quality or value via alternative payment models, 19 physician performance on such measures is of increasing importance to both clinicians and payers.…”
Section: Discussionmentioning
confidence: 99%
“…One study found two measures to be associated with readmission (quality deficiency rating and pressure ulcer rate) 13. Another study found little difference in PPH rates between 1-star and 5-star nursing facilities 14.…”
Section: Introductionmentioning
confidence: 99%